Evaluating Social Return on Investment (SROI) in a Corporate Social Responsibility Program for Riverside SMEs in Post-Pandemic Indonesia: Evidence from the Extractive Sector - Annur, Fajri (Integrasi Sains Media, 2025)
This study evaluates the social, economic, and environmental value generated by a corporate social responsibility (CSR) initiative implemented by a major extractive-industry firm to support riverside micro-entrepreneurs in post-pandemic Indonesia. Utilizing the Social Return on Investment (SROI) framework developed by Social Value UK, the research adopted a mixed-methods approach, combining interviews, focus group discussions, and secondary data collected from 2020 to 2023. The SROI analysis revealed that the program generated a total social benefit of IDR 5.56 billion against an investment of IDR 4.52 billion, yielding an SROI ratio of 1.23. Key outcomes included increased SME turnover, improved hygiene practices verified through certification, and strengthened community resilience. The Theory of Change (ToC) and a self-developed Social Ripple Effect Model for Riverside Micro-Entrepreneurship (SREM-RM) were applied to trace transformation pathways from inputs to long-term impacts. The findings highlight the strategic role of CSR in empowering micro-enterprises during crisis recovery and provide methodological insights for integrating SROI with ToC in impact evaluation. Policy implications emphasize the importance of digital inclusion, institutionalized support systems, and expanded access to microfinance for sustainable SME development.